Performance analysis for canonical Huffman coding with fixed window size. Issue 7 (1st April 2016) - Konstantinides, J.M.; Andreadis, I.
Abstract : The compression efficiency of canonical Huffman coding is drastically affected by the size of the compression window, the choice of which is typically done heuristically analytic bounds for the worst‐case compression efficiency of canonical Huffman coding are introduced, as a function of the size of the compression window. The derived bounds offer fine‐grained control over the compression latency‐efficiency trade‐off.